2001
DOI: 10.1159/000056556
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Sclerotization of Simple Renal Cysts with 95% Ethanol Followed by 24–48 h Drainage with Nephrostomy Tube

Abstract: Aim of the Study: We propose some technique devices for treating simple renal cysts with percutaneous puncture (PCN) to reduce recurrences. Materials and Methods: Between January 1995 and December 1998, a series of 42 patients, 13 females and 29 males, ranging in age between 49 and 73 were treated for symptomatic kidney cystic disease. The cysts varied between 7.4 and 13.6 cm in diameter and from 100 to 570 cm3 in volume. This technique consists of echo-guided emptying of the cyst, and slowly insert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
4

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 1 publication
0
25
0
4
Order By: Relevance
“…While choosing these agents, complications such as infection and hemorrhage, availability, and cost-effectiveness should be considered. Most studies of the agents have revealed that ethanol injection can yield successful results only compared to aspiration (4,9,14). However, the leakage of phenol or ethanol into the surrounding tissues can cause not only minor complications, such as local tissue corrosions, but also major complications, such as aseptic abscess and severe central nervous system depression (9).…”
Section: Discussionmentioning
confidence: 99%
“…While choosing these agents, complications such as infection and hemorrhage, availability, and cost-effectiveness should be considered. Most studies of the agents have revealed that ethanol injection can yield successful results only compared to aspiration (4,9,14). However, the leakage of phenol or ethanol into the surrounding tissues can cause not only minor complications, such as local tissue corrosions, but also major complications, such as aseptic abscess and severe central nervous system depression (9).…”
Section: Discussionmentioning
confidence: 99%
“…Sclerosing agents are believed to produce local inflammation on the luminal surface of cysts and thus result in the adhesion of cyst the walls [4]. Some sclerosing agents; such as glucose, alcohol, pantopaque, phenol, polidocanol, ethanol, bismuth-phosphate, minocycline have been used in other studies [2,3,4,7,8,9,10,12,19]. However, most of them are ineffective or toxic such as pantopaque and have been abandoned at many centers due to reported complications [11,20].…”
Section: Discussionmentioning
confidence: 99%
“…Simple renal cysts are often silent, their progress slow, and they may become symptomatic because of compression on adjacent urinary tract [3]. Large simple renal cysts leading to pain in the lumbar area, renal or pelvic obstruction, and hypertension require intervention [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[120][121][122][123][124][125][126][127][128][129][130][131][132][133][134][135][136] The therapy has been effective in more than 90% of patients after two or three injections. The only direct contraindication to this approach has been a peripelvic cyst.…”
Section: Kidneymentioning
confidence: 99%